Interest Of Junior High School Students In Choosing A Cullinery Major A State Vocational High School 3 Sungai Penuh - Suci Rahmadina; Asmar Yulastri (Jurnal Pendidikan Tata Boga dan Teknologi, 2022)
The research was motivated by the lack Interest Of Junior High School Students In Choosing A Cullinery Major A State Vocational High School 3 Sungai Penuh. This research method is descriptive quantitative. The data on the results of the Of Interest Of Junior High School Students In Choosing A Cullinery Major A State Vocational High School 3 Sungai Penuh. The results of the analysis of research data indicate that the Of Interest Of Junior High School Students In Choosing A Cullinery Major A State Vocational High School 3 Sungai Penuh 35% is in the medium category. The results of the analysis of research data from the will indicator of 41% are included in the medium category. Indicators of feeling happy 38% included in the medium category. The motivation indicator 42% is included in the high category. The indicator of family support 47% is in the medium category. The school environment indicator 40% is in the medium category. 36% of the community environmental indicators are in the low category. The mass media indicator 40% is in the medium category.